Learning Multimodal Transportation Before and After Covid-19 Pandemic - Yeti Komalasari; Fitri Masito; Muhammad Kristiawan; Sudarwan Danim; Syukri Hamzah; Hadiwinarto H (Journal of Innovation in Educational and Cultural Research, 2022)
This study aims to look at the trend of Light Rail Transit (LRT) mass transportation during the covid-19 pandemic as a lesson for multimodal transportation courses. The type of qualitative research that becomes a research instrument is the researcher himself (the author) who is directly involved in the research. The determination of informants in this study uses purposive techniques where only certain people or parties will be used as research objectives as a source of information, namely Informant I: Head of the Section on the Utilization of Facilities and Infrastructure, Informant II: Officials making committees of public service agencies, Informant III: Managers of Passenger Numbers and Revenues, Informant IV: Train Travel Organizers. The results of the study are expected to be able to measure the level of understanding of cadets in the Multiomoda Transportation course. Through the pre-test as the average basis for cadets' knowledge of the Multimodal Transportation course of 87.00, then an intervention was carried out through education and material training based on the results of a research study of light rail transit (LRT) mass transportation trends before and after the Covid-19 Pandemic and a reassessment was carried out to obtain the average post-test results and the results changed to 91.86. Through the Paired Sample T-Test test, the significance value of the pre-test and post-test can be tested, a significance value of 0.000 is obtained, which means that there is a significant difference between the pre-test and post-test values. Furthermore, it can be seen the Correlation value of 0.525 which shows the strength of the relationship of the 2 variables tested, namely pre-test and post-test.